Cheese production ([Lubbock, TX] : CEV Multimedia)
Discover how the phrase 2The Big Cheese3 was coined and by whom. This presentation provides a step-by-step description of the age-old cheese process. Eighteen varieties of cheese (e.g., Brick, Cheddar, Gouda, Limburger, Processed Cheese foods, etc.) are discussed in terms of classification, moisture percentage and method of ripening
System requirements: PC/MAC OSX, Office 2000 or better, IE 5.5, Internet connection, Adobe Acrobat Reader, Flash 5 Player
Keywords: Cheese; Cheese industry